The risk of developing type 2 diabetes mellitus among the students of Hail University, Saudi Arabia - Abd El-Razik Siam, Bahia Glalal; Abdou Rizk, Shimaa Mohamed; Mahmoud, Soha Kamel Mosbah (Frontiers in Public Health, 2023)
Background Globally, it is estimated that approximately 537 million adults are living with diabetes. Of them, more than 90% have type 2 diabetes (T2DM). In 2023, a previous meta-analysis showed that the prevalence of T2DM among the general adult population in Saudi Arabia was 28%. This study was conducted to assess the risk of developing T2DM among the students at Hail University, Saudi Arabia. Methods This cross-sectional study was conducted in 2022/2023 among a census sample of 740 students (both genders, aged 17–26 years) studying at nine colleges of Hail University, Saudi Arabia. The diabetes risk score was assessed using the Australian Type 2 Diabetes Risk Assessment Tool (AUSDRISK). Anthropometric measurements were measured and recorded using standard methods. Socio-demographic variables were also obtained with an interview-based questionnaire. Statistical analysis was performed using SPSS version 25. Results A total of 740 students were included in the final analysis. Of them, 274 (37.0%) were male students and 466 (63.0%) were female students. The mean age of the study participants is 19.9 ± 1.6 years. The findings showed that 61.9% of the study participants were at intermediate and high risk of diabetes (59.7 and 2.2%, respectively). The majority 85.7% of male students were at intermediate risk of diabetes, and 5.8% were at high risk of diabetes. In total, 44.4% of female students were at intermediate risk of diabetes, and none of them were at high risk of diabetes. For the following variables (age, gender, college name, area of the university, academic years, weight, height, and BMI), the differences were statistically significant between different categories of diabetes risk scores (P-values < 0.005). Conclusion More than half of the students at the Hail University of Saudi Arabia have an intermediate and high risk of T2DM. Male students are at a higher risk compared to female students. The high risk of T2DM among university students should be seriously considered.